Strengthening mathematics learning motivation in elementary students through numbered heads together cooperative learning supported by ice-breaking activities - Anggraini Anggraini; Muhammad Fendrik; Intan Kartika Sari (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: Student motivation in elementary mathematics learning often decreases when classroom instruction relies mainly on teacher-centered approaches. Combining cooperative learning with ice-breaking activities may help create a more engaging and emotionally supportive learning environment. Aim: This study aimed to examine whether the Numbered Heads Together cooperative learning model supported by ice-breaking activities could improve students’ motivation to learn mathematics compared to conventional instruction. Method: A quasi-experimental study with a nonequivalent control group design was conducted involving 36 third-grade students from two public elementary schools. The experimental group received mathematics instruction using the Numbered Heads Together model integrated with ice-breaking activities, while the control group was taught using conventional methods. Students’ learning motivation was measured through a validated Likert-scale questionnaire administered before and after the intervention. The data were analyzed using descriptive statistics and an independent samples t-test. Results: Both groups demonstrated an increase in learning motivation after instruction; however, the improvement in the experimental group was higher than that of the control group. Statistical analysis confirmed a significant difference in posttest motivation scores between the two groups. Conclusion: The findings indicate that integrating ice-breaking activities into Numbered Heads Together cooperative learning can strengthen elementary students’ motivation to learn mathematics by fostering active participation and a positive classroom atmosphere.